Guilt and evil in Bolshevism. An approach from the hermeneutic categories of Paul Ricoeur - Herrera Zúñiga, José Roberto (2023)
In the following essay we have analyzed some of the texts and statements of the most significant representatives of Bolshevism, in the light of the Ricœurdian categories of evil and moral guilt. From an immanent analysis of texts we would seek to present a series of fundamental relationships between evil, guilt and political life in bolshevik theory and practice.